2020
DOI: 10.1038/s41598-020-73946-9
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 (TLR4) expression is correlated with T2* iron deposition in response to doxorubicin treatment: cardiotoxicity risk assessment

Abstract: Although doxorubicin (Dox) is an effective antitumor antibiotic in the anthracycline class, it often induces the undesirable side effect of cardiomyopathy leading to congestive heart failure, which limits its clinical use. The primary goal of this study is to evaluate a reliable translational method for Dox-induced cardiotoxicity (CTX) screening, aiming to identify a high-risk population and to discover new strategies to predict and investigate this phenomenon. Early identification of the presence of iron depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Activation of TLR4 signaling in the heart of Cu-intoxicated rats is a direct consequence of excessive ROS generation and cell injury [ 34 ]. Activation of TLR4 occurs in cardiotoxicity, cardiomyopathy, HF, and other cardiac alterations [ 36 ]. TLR4 triggers both the MyD88-dependent and -independent pathways, leading to the activation of transcription factors such as NF-κB and the production of pro-inflammatory mediators [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of TLR4 signaling in the heart of Cu-intoxicated rats is a direct consequence of excessive ROS generation and cell injury [ 34 ]. Activation of TLR4 occurs in cardiotoxicity, cardiomyopathy, HF, and other cardiac alterations [ 36 ]. TLR4 triggers both the MyD88-dependent and -independent pathways, leading to the activation of transcription factors such as NF-κB and the production of pro-inflammatory mediators [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, TLR4 triggers the release of pro-inflammatory mediators through promoting NF-κB and MAPKs [ 35 ]. TLR4 is activated in several cardiac alterations, such as cardiotoxicity, cardiomyopathy, and HF [ 36 ]. However, the possible involvement of TLR4 signaling in Cu cardiotoxicity has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…This DOX-induced iron uptake occurs through a transferrin receptor-dependent mechanism, and the administration of anti-transferrin receptor antibodies dramatically suppress DOX-induced iron uptake, intracellular oxidant production, and cell death. In clinical practice, serum transferrin levels in patients receiving DOX chemotherapy correlate with left ventricular dysfunction severity [118]. Treatment of the HL-1 cell line with DOX caused a time-dependent increase in cytoplasmic and mitochondrial free iron pools, resulting in a loss of mitochondrial membrane potential [102].…”
Section: Apoptosis or Ferroptosis?mentioning
confidence: 99%
“…Clinical studies have shown the important role of systemic TLR4 on cardiac function in patients with hematological malignancy who received a Dox regimen [46,47]. After 6 months of Dox administration, blood sampling was collected to determine TLR4 expression, together with measuring the non-invasive cardiac function in Dox-treated patients [46,47].…”
Section: The Effects Of Dox On Systemic Tlr4 Expression: Reports From...mentioning
confidence: 99%